Female manufacturer-entrepreneurs : the mythical, the true & the new - Lum, Pui Fong (2015)
In recent years, there has been a resurgence of entrepreneurial spirit in Singapore. This is evident on many fronts --- government agencies and programmes for the promotion of entrepreneurship, new magazines and journals that feature the issue of entrepreneurship and the number of international conferences with entrepreneurship as the theme. This resurgent interest in entrepreneurship is the most important economic development of the decade as it sparks off and sustains the economic growth of Singapore. Besides, structural changes in economic and social policies also serve to open the doors to female employment outside the home. Female business owners are emerging as a significant force in the business world, especially in the small- and medium-sized enterprises. However, female entrepreneurship is still in its embryonic stage of development as females are confronted with a number of problems which retard their potential for entrepreneurship. Their progress in this area has been slow compared to their male counterparts. This prompts the researchers to explore the issue of female entrepreneurship. Furthermore, the scope of the research is narrowed down to focus only on the manufacturing sector due to its significance to the Singapore economy. The significance of manufacturing lies in its multiplier effect on the rest of the economy through its strong forward and backward linkages with the other industries. Thus, it is in the national interest that manufacturing should remain as one of the mainstays of the Singapore economy.